Analisis Kepuasan Kerja Karyawan Berdasarkan Human Resource Index (HRI) - Luhur Prayogo; B. Adi Suryo Pranoto; Humiras Hardi Purba (JURNAL TEKNIK INDUSTRI, 2019)
The objective of this research is for describe about employee satisfaction in three of Unit Bisnis at BM*. This topics also for identification many problems of employee satisfaction in BM* and to give suggest for improvement of performance management in this company. Metodology on this research is using a survey, because this method very objective and efficient. Questionnaire besed on Human Resource Index (HRI) with measure 15 attribut. Based on survey HRI of employee in BM* is 3,44. This show that employee satisfaction in BM* is over the standard (> 3) or high. But some of attribute show the HRI which under standard (< 3). Some of this is management quality, organisatin structure and path career, and also company objective. The three of these attribute is problem which need concern on this company.